FRASA VERBA BAHASA TIDORE DALAM TATA BAHASA GENERATIF - Suddin M. Saleh Djumadil (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This study aims at analyzing the structure of Tidore language verb phrase. Descriptive method is used of this study in order to describe the language phenomena in a certain period of time. The data are obtained through recording, elicitation, and retrospection from native speakers (Ahmad Rajak and Sabtu Puha) who settle at the Tidore subdistrict. The basis theory is Generative Grammar. The result of this study indicates that the structures of Tidore language verb phrases are constructed by the transitive verbs as a nucleus which followed by the attributes in the form of noun phrases and followed by noun phrases which can be developed by prepositional phrases and adverbial phrase as well. The positions of nucleus verbs are preceded by objective noun phrases. The transitive verbs of Tidore language have the affixes in the form of prefixes such as yo-, mo-, so-, wo-,. The verb phrases structure rules of Tidore language consist of FV → Spec + V’ + FN + FPrep, FV → Spec + V’ + FN + FAdv, FV → Spec + V’ + FN.